The effect of Al-quran murottal therapy intervention on the patient anxiety levels before tooth extraction procedure at minor surgery clinic: Study quasi experimental - Praptiwi, Yenni Hendriani; Septianingsih, Dewi; Laut, Deru Marah; Widyastuti, Tri (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: The ideal tooth extraction procedure minimizes pain and trauma to the teeth and supporting tissues. The use of sharp instruments like needles, elevators, and forceps can cause discomfort. Listening to murottal Al-Quran and classical music has been proven to reduce patient anxiety, improve physical and mental health, and activate the production of endogenous opioids. The aim of this study is to measure the effect of murottal Al-Quran therapy on the anxiety levels of patients before tooth extraction at the minor surgery clinic of RSGM Unpad. Methods: This quantitative study uses a quasi-experimental method with a non-equivalent control group design. A total of 30 samples were divided into two groups: 15 samples in the experimental group and 15 samples in the control group. Anxiety levels were measured using the Facial Image Scale (FIS) before and after the intervention, and the data was analyzed using the non-parametric Wilcoxon test. Results: The mean difference in anxiety levels in the intervention group before murottal Al-Quran therapy was 0.86, while in the control group with classical music therapy it was 0.33. The mean difference in pulse rates in the intervention group before and after murottal Al-Quran therapy was 6.4, while in the control group with classical music therapy it was 5.47. The Wilcoxon test showed a p-value of 0.002 in the intervention group, indicating p < 0.05. Conclusion: Murottal Al-Quran therapy can reduce patient anxiety before tooth extraction. KEY WORDS: Tooth extraction, dental anxiety, murottal Al-Quran, classical music, Facial Image ScalePengaruh intervensi terapi murottal Al-Quran terhadap tingkat kecemasan pasien pra tindakan ekstraksi gigi di poliklinik bedah minor : studi eksperimental semuABSTRAKPendahuluan: Prosedur pencabutan gigi yang ideal adalah yang minim rasa sakit dan trauma pada gigi serta jaringan pendukungnya. Penggunaan alat tajam seperti jarum, bein, dan yang dapat menyebabkan ketidaknyamanan. Mendengarkan murottal Al-Quran dan musik klasik terbukti menurunkan kecemasan, meningkatkan kesehatan fisik dan mental, serta mengaktifkan produksi opioid endogen. Tujuan penelitian ini adalah mengukur pengaruh terapi murottal Al-Quran terhadap kecemasan pasien sebelum ekstraksi gigi di poliklinik bedah minor RSGM Unpad. Metode: Penelitian kuantitatif ini menggunakan metode quasi-eksperimen dengan desain non-equivalent control group. Total ada 30 sampel yang dibagi menjadi dua kelompok: 15 sampel eksperimen dan 15 sampel kontrol. Tingkat kecemasan diukur menggunakan Facial Image Scale (FIS) sebelum dan sesudah intervensi, dianalisis dengan uji non-parametrik Wilcoxon. Hasil: Rerata selisih kecemasan pada kelompok intervensi sebelum diberi terapi murottal Al-Quran adalah 0,86, sedangkan pada kelompok kontrol dengan terapi musik klasik adalah 0,33. Rerata selisih denyut nadi pada kelompok intervensi sebelum dan sesudah terapi murottal Al-Quran adalah 6,4, sedangkan pada kelompok kontrol dengan terapi musik klasik adalah 5,47. Uji Wilcoxon menunjukkan nilai p sebesar 0,002 pada kelompok intervensi, yang berarti p < 0,05. Simpulan: Terapi murottal Al-Quran dapat menurunkan kecemasan pasien sebelum tindakan ekstraksi gigi.KATA KUNCI: Ekstraksi gigi, kecemasan dental, murottal Al-Quran, musik klasik, Facial Image Scale